Implementasi Akuntansi Lingkungan Dalam Hubungannya Dengan Konsep Triple Bottom Line Menuju Green Economy Guna Mencapai Keberlanjutan Pada PT Varia Usaha Beton (VUB) Sidoarjo - Alifiarisma Maricar; Sunu Priyawan (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
PT. Varia Usaha Beton Sidoarjo is a manufacturing company that produces concrete products and provides services, where the products produced definitely produce a high environmental impact. The application of environmental accounting itself is needed to support the company's operational activities to identify, measure, evaluate and report environmental accounting as control over the responsibility for negative impacts from the company's operational activities. The triple bottom line concept is also a theory that looks not only from the profit aspect but also from the people and planet aspect. This research aims to find out how environmental accounting is implemented in relation to the triple bottom line concept towards a green economy in order to achieve sustainability at PT. Varia Usaha Beton Sidoarjo. This research uses a qualitative descriptive research design with a case study approach. The data in this research was obtained from observations and interviews by researchers with parties related to the research. Based on the results of research at PT. Varia Usaha Beton, it is known that the company has implemented environmental accounting, but the recording carried out does not yet have a separate account. The company has been responsible for managing and minimizing environmental costs to improve company performance, which is related to the triple bottom line concept towards a green economy in order to achieve company sustainability through managing waste and the products produced.